A new species of spiny eel of the genus Notacanthus Bloch 1788 (Notacanthiformes: Notacanthidae) from the Indian Ocean - Idreesbabu Konhamkakkada; Bineesh Kinattumkara; Rajeev Raghavan; Sureshkumar Sivanpillai (Journal of Fish Biology, 2023)
The deep‐sea spiny eels of the genus Notacanthus Bloch 1788 are currently represented by six valid species, of which only one, Notacanthus indicus , has been described so far from the Arabian Sea, part of the Western Indian Ocean. This paper reports the discovery of a new species, described herein as Notacanthus laccadiviensis , from the outer reef drop‐off, off the Kavaratti Island, Lakshadweep Archipelago, Arabian Sea. The new species differs from its congeners in the shape of the head; morphology of dorsal, pectoral and anal fins; number of gill rakers; number of vertebrae; and body colour, and specifically from N. indicus (the only known congener from the Indian Ocean) in the unusual morphology of the dorsal fin, and number of rays in the dorsal and pectoral fins.